2021
DOI: 10.3389/fimmu.2021.756722
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Reveals the Heterogeneity of Tumor-Associated Macrophage in Non-Small Cell Lung Cancer and Differences Between Sexes

Abstract: Non-Small Cell Lung Cancer (NSCLC) is a disease with high morbidity and mortality, which has sex-related differences in prognosis and immunotherapy efficacy. However, the difference in the mechanisms remains unclear. Macrophages, characterized by high plasticity and heterogeneity, act as one of the key cells that exert anti-tumor effects in the tumor microenvironment (TME) and play a complicated role in the process of tumor progression. To elucidate the subtype composition and functional heterogeneity of tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 81 publications
(71 reference statements)
1
57
0
Order By: Relevance
“…IFN-TAMs have high expression of IFN-regulated genes, such as CXCL10 [25,27,28], PDL1 [12,29], and ISG15 [25], and M1-like markers, such as CD86 and MHCII [12]. These TAMs were identified across many tumor types, including breast cancer (BRCA), colorectal cancer (CRC), hepatocellular carcinoma (HCC), head and neck cancer (HNC), lymphoma, melanoma, nasopharyngeal carcinoma (NPC), nonsmall cell lung cancer (NSCLC), ovarian cancer (OVC), pancreatic ductal adenocarcinoma (PDAC), thyroid carcinoma (THCA), uterine corpus endometrial carcinoma (UCEC) [12,25,30,31], multiple myeloma, osteosarcoma, glioblastoma, and spinal ependymomas [32][33][34].…”
Section: Glossarymentioning
confidence: 99%
See 2 more Smart Citations
“…IFN-TAMs have high expression of IFN-regulated genes, such as CXCL10 [25,27,28], PDL1 [12,29], and ISG15 [25], and M1-like markers, such as CD86 and MHCII [12]. These TAMs were identified across many tumor types, including breast cancer (BRCA), colorectal cancer (CRC), hepatocellular carcinoma (HCC), head and neck cancer (HNC), lymphoma, melanoma, nasopharyngeal carcinoma (NPC), nonsmall cell lung cancer (NSCLC), ovarian cancer (OVC), pancreatic ductal adenocarcinoma (PDAC), thyroid carcinoma (THCA), uterine corpus endometrial carcinoma (UCEC) [12,25,30,31], multiple myeloma, osteosarcoma, glioblastoma, and spinal ependymomas [32][33][34].…”
Section: Glossarymentioning
confidence: 99%
“…These TAMs have been identified in BRCA, CRC, NSCLC, NPC, OVC, PDAC, THCA, and UCEC [25,30,31]. Through SCENIC and single-sample gene-set enrichment analysis (ssGSEA) analysis of scRNA-seq data from these cancer types, transcription factors CEBPB, FOSL2, and HIFA were predicted to regulate the expression of this gene signature [25,27,28,30,31,49,50]. In some cancer types, instead of expressing SPP1, Angio-TAMs express other marker genes, including VCAN in BRCA and melanoma, INHBA in gastric cancer and ESCA, and FN1 in kidney cancer [25].…”
Section: Glossarymentioning
confidence: 99%
See 1 more Smart Citation
“…These new tumor antigens can not only enhance the immune response of T cells, but also increase the content of new antigen-specific T cells, thus improving the immune system's ability to identify tumors (32). Studies have shown that the mutation of the DDR pathway will result in the production of higher TMB and neoantigen loads, thus significantly improving the effectiveness of ICI treatment (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid cells are a heterogeneous [ 3 , 21 ] population of innate immune cells that constitute more than 70% of all immune cell populations in the TME [ 22 ]. Common myeloid progenitor cells give rise to macrophages, myeloid-derived suppressor cells (MDSC), granulocytes, dendritic cells (DC), and neutrophils [ 23 , 24 ].…”
Section: Function Of Tumor-associated Macrophages (Tam) In Tmementioning
confidence: 99%